2016
DOI: 10.1016/j.celrep.2016.01.005
|View full text |Cite|
|
Sign up to set email alerts
|

Condensin and Hmo1 Mediate a Starvation-Induced Transcriptional Position Effect within the Ribosomal DNA Array

Abstract: Summary Repetitive DNA arrays are important structural features of eukaryotic genomes that are often heterochromatinized to suppress repeat instability. It is unclear, however, if all repeats within an array are equally subject to heterochromatin formation and gene silencing. Here, we show that in starving Saccharomyces cerevisiae, silencing of reporter genes within the ribosomal DNA (rDNA) array is less pronounced in outer repeats compared to inner repeats. This position effect is linked to the starvation-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 40 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…As noted above, several previous studies have shown HMO1 binding either across the rDNA or with a preferred association with transcribed regions, depending on method of detection, ChIP protocol, and normalization strategy (148)(149)(150)155). In contrast, Wang et al (154) reported limited HMO1 binding to 35S rRNA genes in log-phase cells (4 h of growth following inoculation of cultures) and an ϳ6-fold enrichment during nutrient limitation (24 h of growth); whether the failure to detect HMO1 binding in log-phase cells is due to variations in ChIP protocols or to the genetic background is not clear. The basis for these differences notwithstanding, the reported increase in HMO1 binding upon nutrient limitation would be consistent with a contribution of HMO1 to rDNA compaction under such conditions.…”
Section: Hmo1 Is a Component Of The Pol I Transcription Machinerymentioning
confidence: 72%
See 3 more Smart Citations
“…As noted above, several previous studies have shown HMO1 binding either across the rDNA or with a preferred association with transcribed regions, depending on method of detection, ChIP protocol, and normalization strategy (148)(149)(150)155). In contrast, Wang et al (154) reported limited HMO1 binding to 35S rRNA genes in log-phase cells (4 h of growth following inoculation of cultures) and an ϳ6-fold enrichment during nutrient limitation (24 h of growth); whether the failure to detect HMO1 binding in log-phase cells is due to variations in ChIP protocols or to the genetic background is not clear. The basis for these differences notwithstanding, the reported increase in HMO1 binding upon nutrient limitation would be consistent with a contribution of HMO1 to rDNA compaction under such conditions.…”
Section: Hmo1 Is a Component Of The Pol I Transcription Machinerymentioning
confidence: 72%
“…Rapamycin treatment has also been reported to result in the dissociation of HMO1 from rDNA, and TORC1-dependent repression of rDNA transcription is reduced in the absence of HMO1, suggesting a role for HMO1 in communicating TORC1 activity (150). Nutrient limitation is a condition expected to inhibit TORC1; as noted above, a recent study suggested that nutrient limitation (achieved by growing yeast cells for 24 h following inoculation) resulted in increased HMO1 binding to rDNA and to nucleolar contraction (154). It would be instructive to determine TORC1 activity after 24 h of growth compared to the more extensive depletion of nutrients and to investigate if increased HMO1 binding to rDNA may be a transient phenomenon.…”
Section: Hmo1 Coordinates Responses To Torc1 Signalingmentioning
confidence: 95%
See 2 more Smart Citations
“…He et al found that disruption of Cut3 alters the profile of position-dependent transcription in otr3L tandem array without total loss of silencing, suggesting that Cut3 functions as an upstream regulator of this position effect. Wang et al also showed that condensin is essential for the position effect in rDNA tandem repeat in budding yeast, indicating that the role of condensin in regulating the organization of DNA repeats is conserved (Wang et al, 2016). …”
Section: Mechanisms Regulating Position Effect In Tandem Repeatsmentioning
confidence: 99%